High Proportions of Patients With Advanced HIV Are Antiretroviral Therapy Experienced: Hospitalization Outcomes From 2 Sub-Saharan African Sites. (4th March 2018) - Ousley, Janet; Niyibizi, Aline Aurore; Wanjala, Stephen; Vandenbulcke, Alexandra; Kirubi, Beatrice; Omwoyo, Willis; Price, Janthimala; Salumu, Leon; Szumilin, Elisabeth; Spiers, Sofie; van Cutsem, Gilles; Mashako, Maria; et al.
Abstract: Background: Human immunodeficiency virus (HIV) remains an important cause of hospitalization and death in low- and middle- income countries. Yet morbidity and in-hospital mortality patterns remain poorly characterized, with prior antiretroviral therapy (ART) exposure and treatment failure status largely unknown. Methods: We studied HIV-infected inpatients aged ≥13 years from cohorts in Kenya and the Democratic Republic of Congo (DRC), assessing clinical and demographic characteristics and hospitalization outcomes. Kenyan inpatients were prospectively enrolled during hospitalization; identical retrospective data were extracted for Congolese patients meeting the study criteria using routine medical information. Results: Among 338 HIV-infected patients in Kenya and 411 in DRC, 83.7% (95% confidence interval [CI], 79.4%–87.3%) and 97.3% (95% CI, 95.2%–98.5%), were admitted with advanced disease (defined as CD4 <200 cells/µL or World Health Organization stage 3/4 illness). Among inpatients with advanced HIV, 35.4% and 21.7% were ART-naive at admission. Patients under care had a median time of 44.1 (interquartile range [IQR], 18.4–90.5) months and 55.9 (IQR, 28.1–99.6) months on treatment; 17.2% (95% CI, 13.5%–21.6%) and 29.6% (95% CI, 25.4%–34.3%) died, 25.9% (95% CI, 16.0%–39.0%) and 22.5% (95% CI, 15.8%–31.0%) of these within 48 hours. Conclusions: Across 2 diverse clinical contexts in sub-Saharan Africa, advanced HIV inpatients were frequently admitted with low CD4 counts, often failing first-line ART. Earlier identification of treatment failure and rapid switching to second-line ART are needed.